Corak pencapaian pelajar kumpulan pertama sistem pendidikan berasaskan hasil Fakulti Kejuruteraan Universiti Kebangsaan Malaysia - Azami Zaharim,; Mohd Marzuki Mustafa,; Khamisah Jafar,; Norhamidi Muhamad, (Penerbit Universiti Kebangsaan Malaysia, 2009)
In accordance with the requirements of The Board of Engineers Malaysia and The Ministry of Higher Education of Malaysia, in the 2005/2006 academic session, the Faculty of Engineeering UKM started implementing the Outcome Based Education (OBE) approach for its undergraduates curriculum, involving some changes in the teaching mehods and syllabus for a number of Þrst and second year courses. A committee has been set up at the faculty to continuously monitor the efÞciency and effectiveness of this effort. This paper explains one of the results obtained, namely the CGPA achievements pattern of students who had undergone the new curriculum for four semesters. The study involves 391 second year students from the 2006/2007 academic session. Students were categorized according to department, sex, and entrance CGPA, which divides students based on their pre-university background namely Matriculation, STPM, Special Science Case, and Special Case. One of the interesting result reports that female students generally achieve better results than the male students in the Þrst two years of study